PENGEMBANGAN METODE PENGUMPULAN DATA PERJALANAN BERBASIS AKTIVITAS DAN LOKASI - Hadi, Prayoga Luthfil; Joewono, Tri Basuki (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Travel analyses based on activity and location have not been well established in Indonesia yet since its complexity in the process of data collection and the needed resources. Thus, it is needed an effort to develop a method of data collection to facilitate future research. This study aims to develop a method of data collection regarding travel based activity and location with limited resources for application in Indonesia. Result of study shows that the proposed method is able to collect the needed data using limited technology and resources.